Promoting Pancasila ideology through comic based learning media - Rahmawati, Selly; Sundari, Nanda Dewi; Hassan, Nurul Asyikin Binti; Permana, Septian Aji (Universitas Negeri Yogyakarta, 2024)
This research's objectives are to 1) develop a storybook with a picture (comic) as a learning media for Pancasila and Civic Education (PCE) and 2) to evaluate its effectiveness in improving the learning results of grade V elementary school students in learning the values of Pancasila. This is research and development by implementing the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research's subjects are 27 students of V (A), 28 students of V (B) and eight students of V (C) as experiment, control, and limited test classes, respectively. The result of the development found that the product, a book with pictures, is suitable for learning after being evaluated by a media expert and a material expert with evaluations of 99 and 71, respectively. The effectivity evaluation was conducted using a t-test on the experiment and control classes with sig. value of 0.000<0.005. The post-test results from the experiment and control classes are 70.64 and 60.93, respectively, which shows that the experiment class had higher mean results than the control class. The research concluded that the storybook with pictures is effective and suitable for enhancing the students' learning achievement.